Objective Methods in the Assessment of Child Language Development in Natural Settings and Using Testing - Marina A. Zhukova; Victoria A. Manasevich; Irina V. Golovanova; Pavel I. Letyagin; Taisia A. Ulianova; Sofia S. Tikhonova (Peoples' Friendship University of Russia (RUDN University), 2022)
The authors describe the application of various approaches to the assessment of child language development reviewing the methods most widely used in research and clinical practice. The review outlines the benefits and some limitations of longitudinal method of assessment using language recordings, language corpus analysis and transcripts of speech samples. Technical aspects of the linguistic environment recordings using LENA technology, which allows to achieve ecologic validity in the assessment of children's language environment, are considered. Analysis of the corpus data through the transcription of the dialogues between children and adults are discussed, as well as the study of linguistic parameters of child speech in comparison to a normative group of peers. The authors offer a review of the most widely known parent reports, questionnaires, and maximum performance testing of children's language development. Among the assessment tools available for Russian-speaking populations McArthur-Bates CDI and PLS-5 are reviewed. The authors note an importance of integration of Russian research into the international scientific knowledgebase through the adaptation of methods for assessment of language development in children.